Basotho herders learn through culture and social interaction. (June 2017) - Pitikoe, Selloane
Abstract: Livestock herding practice is globally viewed as a male responsibility which males learn at a young age and hence, limits education access. The study probes the cultural influence of herding on male herders and perhaps its influence on their learning preferences and styles. The study further explores the resourcefulness of social relationships in enhancing further literacy learning among the herders. Drawing on the social capital concept, this study seeks to explore its instrumentality in influencing learning. The interviews; transect walks and photo voice were employed to collect data on a group of 30 purposively sampled adult male Basotho herders. Results show that; herding is a rich learning resource of indigenous knowledge (IK). The study suggests a holistic non-formal education (NFE) provision that embraces the herders (lifestyles, social networks as well as IK practices) and a need for NFE policy and practice to explore the relevance of social literacy in its programming.